2009
DOI: 10.1093/sleep/32.6.760
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Blood Pressure in Normotensive Subjects With Chronic Insomnia: Implications for Cardiovascular Risk

Abstract: Higher nighttime SBP and blunted day-to-night SBP dipping are present in normotensive subjects with chronic insomnia and are associated with a hyperactivity of the central nervous system during sleep. An altered BP profile in insomniacs could be one mechanism implicated in the link between insomnia and cardiovascular morbidity and mortality documented in epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 175 publications
(110 citation statements)
references
References 37 publications
7
96
1
6
Order By: Relevance
“…Decreased SWS is associated with a 1.8‐fold increased risk of developing hypertension in elderly men (Fung et al, 2011). The circadian rhythm of BP is blunted in patients with insomnia, even in those who are normotensive (Lanfranchi et al, 2009). Inversely, non‐dippers have poor quality of sleep (Pedulla et al, 1995).…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…Decreased SWS is associated with a 1.8‐fold increased risk of developing hypertension in elderly men (Fung et al, 2011). The circadian rhythm of BP is blunted in patients with insomnia, even in those who are normotensive (Lanfranchi et al, 2009). Inversely, non‐dippers have poor quality of sleep (Pedulla et al, 1995).…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…Chronic insomnia is associated with elevated nocturnal systolic blood pressure and reduced day-to-night blood pressure dipping [78]. Chronic insomnia is also considered a significant risk factor in the development of mild to moderate hypertension [79,80].…”
Section: Long-term Consequences Of Insomniamentioning
confidence: 99%
“…[8][9][10] Earlier studies have indicated that there is an association between insomnia and hypertension incidence. [11][12][13] In a study in Chinese population, the prevalence of hypertension in those with no insomnia, occasional insomnia and frequent insomnia was reported to be 37.3%, 43.0% and 48.0% respectively.…”
Section: Introductionmentioning
confidence: 99%